Multilingual Children's Mathematical Reasoning - Assaf, Fatima (Université d'Ottawa / University of Ottawa, 2014)
This research adopts a sociocultural framework (Vygotsky, 1978) to investigate how multilingual children express their mathematical reasoning during collaborative problem solving. The topic is important because North America is becoming increasingly multicultural, and according to mathematics teachers this has complicated the challenges of teaching and learning mathematics. Many educators assume that children should be competent in the language of instruction before they engage with mathematical content (Civil, 2008; Gorgorió & Planas, 2001). A review of recent research in this area challenges the idea that multilingual students need to have mastered the official language of instruction prior to learning mathematics (Barwell, 2005; Civil, 2008; Moschkovich, 2007). These researchers demonstrate that the knowledge of the language of instruction is only one aspect of becoming competent in mathematics. My research was designed to build on the findings of the current research on multilingual children’s reasoning in order to more fully understand how multilingual children express their mathematical understanding and reasoning. For this study, two multilingual families, each with 3 children between the ages of 8 and 12, participated in a mathematical problem-solving activity. Findings show the children’s mathematical reasoning was evidence-based drawing on mathematical knowledge and world knowledge.
Keywords: Mathematics; Multilingual learners; Reasoning; Problem solving; Collaboration